Surgery for Chest Wall Deformities - Raff, Gary W.; Hirose, Shinjiro (Springer International Publishing : Imprint: Springer, 2017)
This book was conceived and written to provide a contemporary view of critical urban transport issues, policies, and initiatives in twelve countries with emerging economies, each at somewhat different stages of development. With dedicated chapters on Brazil, China, Colombia, India, Indonesia, Iran, Mexico, Nigeria, Russia, South Africa, Turkey, and Vietnam, the book contains detailed, comparable information about the current urban transport situation in the major cities in these countries. Written by specialists in the field, the book draws on a wide range of information sources to provide up-to-date accounts of each of these countries. By assembling this information in one volume, it provides a valuable source for academics as well as policy-makers with an interest in the current and emerging urban transport needs of a large portion of the world's population.